Honouring Water: The Mistawasis Nêhiyawak Water Governance Framework - Mora, Maria F.; Johnston, Anthony B. D.; Watson, Michelle; Bharadwaj, Lalita (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
Collaborative water governance in Indigenous territories requires the building of a nation-to-nation relationship where different water worldviews and knowledges are acknowledged, valued, and included in water governance. This article presents the Mistawasis Nêhiyawak Honour the Water Governance Framework, an alternative collaborative water governance approach in Saskatchewan, Canada. The Nêhiyawak principles, identity, knowledge, and self-determination are its foundation. Equitable dialogue is the central axis. The framework represents an alternative water governance structure to the current Canadian system that may more effectively respond to the water challenges of this First Nation. This framework supports the appeal from Mistawasis First Nation and other Nations, for the de-construction of hegemonic colonial water governance systems towards the co-construction of shared processes of water participation, decision-making, and responsibility.